Driving a Circular Economy: Nudging and Innovative Strategies for Promoting Post-Consumer Recycled Plastic Home-Appliances - Nikolas Neumann; Aline Mangold; Julia Schneider; Christian Wölfel (Circular Economy and Sustainability, 2025)
The various social and ecological crises of our time are leading to ever louder calls for a sustainable transition towards a sustainable circular economy. As a result, the recycling of plastics is increasingly being brought to the foreground and the increased use of post-consumer recyclate (PCR) is being called for. However, the acceptance of products made from PCR plastic and how this can be increased is still largely unclear. This study uses a light switch to investigate the purchase intention and willingness to pay for household appliances made of (supposed) PCR plastic and how this can be increased with the help of nudges and guideline-based cues. In addition, the influence of a sustainability attitude is examined. An experimental study using a single-factor between-subjects study design ( n = 90) with six different cues has been conducted. A light switch made of (supposed) PCR plastic was used as a stimulus. The study results indicate that the purchase intention for PCR-based household appliances can be significantly increased using specific informational cues. Of the five cues tested, only one (innovation) did not lead to a significant increase in purchase intention when compared to the baseline cue. Contrary, none of the five cues led to a significant increase in willingness to pay when compared to the baseline cue. No significant moderating effect of sustainability attitude was found in either case. Possible explanations for these results are the attitude-behavior-intention gap and the influence of perceived aesthetics.

Nitrogen isotope values of Pennisetum glaucum (pearl millet) grains: towards a reconstruction of past cultivation conditions in the Sahel, West Africa - Amy K. Styring; Amadou M. Diop; Amy Bogaard; Louis Champion; Dorian Q. Fuller; Nikolas Gestrich; Kevin C. Macdonald; Katharina Neumann (Vegetation History and Archaeobotany, 2019)